PENERAPAN BOUNDED INQUIRY LABORATORY UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS PESERTA DIDIK KELAS XI MIA 2 SMA N 1 SUKOHARJO - Alfiani Viki Sutanto; Suciati Sudarisman; Nurmiyati Nurmiyati (Universitas Sebelas Maret, 2015)
The research aimed to improve students’ science process skills through bounded inquiry laboratory model in biological learning process on 2nd grade of science 2 at SMA N 1 Sukoharjo in Academic Year 2014/2015. The research belongs to classroom action research consist of two cycle and each have four phases, namely: planning, actuating, observing, and reflecting. Research was carried out on four aspects of the students’ science process skills that includes aspects of measuring, formulating the problem, formulating hypotheses and experimental plan to achieve an increase of 20%. The Subject of this research is 2nd grade 38 students of science 2 at SMA N 1 Sukoharjo. Sources of data obtained from the teacher and students. Test and non test technics were used to collect the data. It was carried out by using question test science process skills, observation, and interview. The obtained data were analyzed using descriptive qualitative method consist of three components , namely: data reduction, data presentation, and conclusion or verification. Validated through using triangulation method. The method of research was spiral method. The result showed that bounded inquiry laboratory able to improve four aspects of student’s science process skills from Pre-Cycle, 1st Cycle and 2nd Cycle, such as: 1) in aspect measuring (32,00%, 74,48%, 86,57%) achieve an increase of 54,57%; 2) formulating the problem (25,72%, 73,42%, 91,58%) achieve an increase of 65,86%; 3) formulating hypotheses (24,00%, 83,69%, 94,31%) achieve an increase of 70,31%; 4) experimental plan (13,72%, 74,00%, 85,31%) achieve an increase of 71,59%. Therefore, it can be concluded that Bounded Inquiry Laboratory in biological learning process could improved students’ science process skills more than 20% on 2nd grade students of science 2 at SMA N 1 Sukoharjo in Academic Year 2014/2015. Keywords: bounded inquiry laboratory model, science process skills